ANALISIS KETERAMPILAN MENULIS KARANGAN DESKRIPSI MENGGUNAKAN METODE OUTDOOR STUDY PADA PESERTA DIDIK KELAS IV UPTD SD NEGERI ALAANG - Yelena Weni Gati; Yermia S. Wabang; Antonius A. Saetban (STKIP Subang, 2026)
This study aims to describe the descriptive writing skills of fourth-grade students at UPTD SD Negeri Alaang through the application of the Outdoor Study method. The background of this study is the students' low ability in writing descriptive essays, shown by difficulties in developing ideas, constructing sentences, choosing appropriate vocabulary, and applying spelling and punctuation rules. This research employed a qualitative approach with a descriptive research type. The subjects were 20 fourth-grade students. Data were collected through observation, tests, and documentation, and analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results show that before the implementation of the Outdoor Study method, most students experienced difficulties in writing descriptive essays, particularly in the use of capital letters, spelling, punctuation, vocabulary choice, and paragraph development. After implementing the Outdoor Study method through direct observation of rice fields and the beach, students became more active in observing objects, gained authentic experience, and found it easier to translate their observations into more detailed and coherent descriptive writing. This study concludes that the Outdoor Study method provides a meaningful learning experience and is effective in improving students' descriptive writing skills.